2020
DOI: 10.1002/ppul.25069
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Severity Score greater than or equal to 2 at birth is associated with an increased risk of mortality in infants with birth weights less than or equal to 1250 g

Abstract: Objective Respiratory Severity Score (RSS), the product of mean airway pressure and the fraction of inspired oxygen may estimate the severity of neonatal lung disease. We aimed to determine if RSS on the first day of life is associated with mortality and/or comorbidities in infants born less than or equal to 1250 g. Methods Data were extracted from the NYS Perinatal Data System for premature inborn infants from 2006 to 2016 born between 400 and 1250 g (N = 730). RSS was divided into three categories: less than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…An arterial access may not be routinely performed in mildly to moderately ill newborns due to the risks associated with it. Studies have assessed the e cacy of using modi ed versions of OI, such as oxygenation saturation index (OSI, replacing PaO 2 with blood oxygen saturation using pulse oximetry, or SpO 2 , in index calculation) or respiratory severity scores (RSS, the product of MAP and FiO 2 ) as surrogate markers for pulmonary illness [28][29][30][31][32][33][34]. One recent study showed a strong correlation between OI and OSI in the neonatal population [32].…”
Section: Discussionmentioning
confidence: 99%
“…An arterial access may not be routinely performed in mildly to moderately ill newborns due to the risks associated with it. Studies have assessed the e cacy of using modi ed versions of OI, such as oxygenation saturation index (OSI, replacing PaO 2 with blood oxygen saturation using pulse oximetry, or SpO 2 , in index calculation) or respiratory severity scores (RSS, the product of MAP and FiO 2 ) as surrogate markers for pulmonary illness [28][29][30][31][32][33][34]. One recent study showed a strong correlation between OI and OSI in the neonatal population [32].…”
Section: Discussionmentioning
confidence: 99%
“…[ 18 , 19 ] Furthermore, several studies have shown its predictive value for mortality, BPD, and other short-term morbidities. [ 20 , 21 , 23 ] Mhanna et al . [ 22 ] investigated the utility of RSS for predicting extubation readiness in very-low-birth-weight infants and found that it was the only statistically significant risk factor for extubation failure.…”
Section: Discussionmentioning
confidence: 99%
“…It has been used as a measure of disease severity in some large-scale multicenter studies. [ 18 , 19 ] In addition, its association with BPD, mortality, and short-term complications has been investigated,[ 20 , 21 ] and high RSS values were found to be associated with extubation failure. [ 22 ] A study in which the RSS was analyzed by weight (RSS/kg) found that RSS/kg was more useful for predicting the development of pulmonary hypertension than the RSS.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies exploring the predictive role of RSS involved patients who required invasive MV. In Shah et al's study (17), NCPAP pressure was considered equal to MAP in infants requiring nasal continuous positive airway pressure (NCPAP) in the birth room with no need for subse-quent MV. These authors found that a RSS of ≥ 2 on the first postnatal day was associated with increased morbidity and mortality in infants weighing ≤ 1250 g. On the other hand, in infants undergoing NCPAP or nasal positive pressure ventilation (NIPPV) therapy, the ventilator settings for PEEP/MAP are not equal to the achieved MAP (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…RSS has been shown to closely correlate with OI in newborns receiving mechanical ventilation (12) and has been utilized as a measure of disease severity in several large-scale, multi-center studies (13,14). Further areas of previous research include the role of RSS in preparation for extubation as well as in the prediction of BPD, mortality, and short-term complications (15)(16)(17). Also, it has been found that RSS/kg is correlated more closely with pulmonary hypertension than RSS alone (18).…”
Section: Introductionmentioning
confidence: 99%